PENGARUH PERLAKUAN SECARA KIMIAWI (AMONIASI) DAN BIOLOGI (KAPANG) PADA KULIT KOPI TERHADAP KECERNAAN BAHAN KERING DAN KECERNAAN BAHAN ORGANIK (IN VITRO) - Laily Miftakhul Muna, Muhtarudin, Rudy Sutrisna, dan Farida Fathul (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2019)
The purpose of this research was 1) to compare the effect of chemical (ammoniation) and biological (mold) treatment on coffee husk to dry matter and organic matter digestibility in vitro; 2) knowing the best parameters of the quality on coffee husk processed biologically and chemically on the dry matter and organic matter digestibility in vitro. The research was conducted on 31th of December 2018 until 01st of March 2019 at the Laboratory of Animal Nutrition and Food Laboratory, Department of Animal Husbandry, University of Lampung; Microbiology Laboratory of FMIPA Lampung University and Dairy Animal Nutrition Science Laboratory, Faculty of Animal Husbandry, Bogor Agricultural University. This study used completely randomized design (CRD) with 4 treatments and 3 replications. The treatments given in this study were coffee husk without treatment (P1), coffee husk with 4% urea (P2), coffee husk with 1.5% ammonium sulfate (P3), coffee husk with Aspergillus niger 5 gram (P4). The results showed that ammoniation and fermentation treatment significantly effect (P<0,01) for dry matter digestibility and digestibility of organic matter. The best treatment of coffee husk on dry matter digestibility and organic matter digestibility is by adding 4% urea. Keywords: Coffee husk, Ammoniation, Fermentation, Dry matter digestibility, Organic matter digestibility.